Learning Cluster as a Modern Requirement for Optimizing Vocational Training of Future Specialist - Borisenko, D. (Problems of Engineer-Pedagogical Education, 2019)
Training of future specialist demands reorientation of the educational process towards modern requirements of the industry, establishment of close partnership of educational institutions with industrial enterprises, and creation of clusters. The article considers features of the organization of an educational cluster on the example of vocational training of future specialists in design as well as peculiarities of practical optimization of the educational process. Its application in the educational process makes it possible to achieve joint studying of separate disciplines by students of different specialties, promotes students’ interaction while working on term papers or individual practical, laboratory, scientific and methodological projects, helps expand borders of the educational environment, and allows transition to a more professional level of training. The paper defines advantages of organizing an educational cluster and peculiarities of its implementation at the selected levels of optimization of the educational process, which are as follows: level of an educational institution, level of a structural division, specialty level, level of a training program and level of an academic discipline. The concepts "educational cluster" and "educational cluster" are differentiated. Special attention is directed to the organization of the research educational clusters integrating not only students of educational institutions, but also skilled workers of the industrial enterprises, researchers and practioners. Clusters play an important role in exchanging professional experience, implementing new approaches, techniques and technologies of training, incorporating innovative methodological, technical complexes and means as well as information and communication technology, presenting the outcomes of practical approbation of new training technologies by teachers. Theoretical consideration of the features of the organization of an educational cluster has led to a suggestion concerning its practical embodiment in the educational process and further detailed research on the aspects of enhancing the quality of vocational training and future specialists’ competitiveness in the modern labor market as well as improving teachers’ pedagogical skills and qualifications.